Switching on the green light for chimeric antigen receptor T‐cell therapy - Sherly Mardiana; Junyun Lai; Imran Geoffrey House; Paul Andrew Beavis; Phillip Kevin Darcy (Clinical & Translational Immunology, 2019)
Abstract Adoptive cellular therapy involving genetic modification of T cells with chimeric antigen receptor (CAR) transgene offers a promising strategy to broaden the efficacy of this approach for the effective treatment of cancer. Although remarkable antitumor responses have been observed following CAR T‐cell therapy in a subset of B‐cell malignancies, this has yet to be extended in the context of solid cancers. A number of promising strategies involving reprogramming the tumor microenvironment, increasing the specificity and safety of gene‐modified T cells and harnessing the endogenous immune response have been tested in preclinical models that may have a significant impact in patients with solid cancers. This review will discuss these exciting new developments and the challenges that must be overcome to deliver a more sustained and potent therapeutic response.